Documenting factors related to examination stress among school children in Surat city - Buch, Rutu Sanjaybhai; Vyas, Shailee N.; Moitra, Mohua (International Journal Of Community Medicine And Public Health, 2019)
Background: Academic examinations have been considered as one of the acute stresses experienced by students. Passing or failing has strong consequences, so examinations cause psychological stress for most students. This study designed to document stressors and anti-stressors related to exam and quantify the stress. Methods: A cross sectional study using purposive sampling was carried out involving 387 secondary and higher secondary school students. Beck Anxiety Inventory (BAI) and semi-structured questionnaire was used to collect data. Results: Among the respondents, 76.7% felt that exams should be taken. Worry (46.8%); fear of forgetting (24.3%), nervousness (14.7%) and fear (10.1%) were the common stressors. Exams were a positive opportunity to prove their mettle was shared by 23.3% students. Stress level was constant among 50.9% of participants irrespective of the level of their preparation. MCQ (51.2%) was the preferred examination pattern. In majority (74.4%) failing equated obtaining less marks. Fear of failing existed among 46.5% participants. Mean score for BAI was 10.15 with participants falling into mild (92.7%), moderate (6.5%) and severe (0.8%) stress categories. A total of 68% students felt that these stresses can be reduced. Preferred way to relax was talking to friends (55.6%), listening to music (53.5%) and watching TV (47%). Most helpful person was the mother (39%). Parental reaction to stress was generally supportive (63.6%). Professional counselling was taken by 2.6% students. Conclusions: Exams were associated with worry, nervousness and fear. Fear of failure added to this stress. However, parents were generally supportive. Mean BAI score was 10.15.